login
This site is supported by donations to The OEIS Foundation.

 

Logo

Please make a donation to keep the OEIS running. We are now in our 55th year. In the past year we added 12000 new sequences and reached 8000 citations (which often say "discovered thanks to the OEIS"). We need to raise money to hire someone to manage submissions, which would reduce the load on our editors and speed up editing.
Other ways to donate

Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A057078 Periodic sequence 1,0,-1,...; expansion of (1+x)/(1+x+x^2). 42

%I

%S 1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,

%T -1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,

%U 0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1,1,0,-1

%N Periodic sequence 1,0,-1,...; expansion of (1+x)/(1+x+x^2).

%C Partial sums of signed sequence is shifted unsigned one: |a(n+2)|= A011655(n+1).

%C With interpolated zeros, a(n) = sin(5*Pi*n/6 + Pi/3)/sqrt(3) + cos(Pi*n/6 + Pi/6)/sqrt(3); this gives the diagonal sums of the Riordan array (1-x^2, x(1-x^2)). - _Paul Barry_, Feb 02 2005

%C From _Tom Copeland_, Nov 02 2014: (Start)

%C With a shift and a sign change the o.g.f of this array becomes the compositional inverse of the shifted Motzkin or Riordan numbers A005043,

%C (x - x^2) / (1 - x + x^2) = x*(1-x) / (1 - x*(1-x)) = x*(1-x) + [x*(1-x)]^2 + ... . Expanding each term of this series and arranging like powers of x in columns gives skewed rows of the Pascal triangle and reading along the columns gives (mod-signs and indexing) A011973, A169803, and A115139 (see also A091867, A092865, A098925, and A102426 for these term-by-term expansions and A030528). (End)

%H Ralph E. Griswold, <a href="http://www.cs.arizona.edu/patterns/sequences.html">Shaft Sequences</a>

%H <a href="/index/Ch#Cheby">Index entries for sequences related to Chebyshev polynomials.</a>

%H <a href="/index/Rec#order_02">Index entries for linear recurrences with constant coefficients</a>, signature (-1,-1).

%F a(n) = S(n, -1) + S(n - 1, -1) = S(2*n, 1); S(n, x) := U(n, x/2), Chebyshev polynomials of 2nd kind, A049310. S(n, -1) = A049347(n). S(n, 1)= A010892(n).

%F From Mario Catalani (mario.catalani(AT)unito.it), Jan 08 2003: (Start)

%F a(n) = (1/2)*((-1)^floor(2*n/3) + (-1)^floor((2*n+1)/3)).

%F a(n) = -a(n-1) - a(n-2).

%F a(n) = A061347(n) - A049347(n+2). (End)

%F a(n) = Sum_{k=0..n} binomial(n+k, 2k)*(-1)^(n-k) = Sum_{k=0..floor((n+1)/2)} binomial(n+1-k, k)*(-1)^(n-k). - Mario Catalani (mario.catalani(AT)unito.it), Aug 20 2003

%F Binomial transform is A010892. a(n) = 2*sqrt(3)*sin(2*Pi*n/3 + Pi/3)/3. - _Paul Barry_, Sep 13 2003

%F a(n) = cos(2*Pi*n/3) + sin(2*Pi*n/3)/sqrt(3). - _Paul Barry_, Oct 27 2004

%F a(n) = Sum_{k=0..n} (-1)^A010060(2n-2k)*(binomial(2n-k, k) mod 2). - _Paul Barry_, Dec 11 2004

%F a(n) = -(1/3)*(2*(n mod 3) - (n+1) mod 3 - (n+2) mod 3). - _Paolo P. Lava_, Oct 09 2006

%F a(n) = (4/3)*(|sin(Pi*(n-2)/3)| - |sin(Pi*n/3)|)*|sin(Pi*(n-1)/3)|. - _Hieronymus Fischer_, Jun 27 2007

%F a(n) = 1 - (n mod 3) = 1 + 3*floor(n/3)) - n. - _Hieronymus Fischer_, Jun 27 2007

%F a(n) = 1 - A010872(n) = 1 + 3*A002264(n) - n. - _Hieronymus Fischer_, Jun 27 2007

%F Euler transform of length 3 sequence [0, -1, 1]. - _Michael Somos_, Oct 15 2008

%F a(n) = a(n-1)^2 - a(n-2)^2 with a(0) = 1, a(1) = 0. - _Francesco Daddi_, Aug 02 2011

%F a(n) = A049347(n) + A049347(n-1). - _R. J. Mathar_, Jun 26 2013

%e 1 - x^2 + x^3 - x^5 + x^6 - x^8 + x^9 - x^11 + x^12 - x^14 + x^15 + ...

%p A057078:=n->1-(n mod 3); seq(A057078(n), n=0..100); # _Wesley Ivan Hurt_, Dec 06 2013

%t a[n_] := {1, 0, -1}[[Mod[n, 3] + 1]] (* _Jean-Fran├žois Alcover_, Jul 05 2013 *)

%t CoefficientList[Series[(1 + x) / (1 + x + x^2), {x, 0, 40}], x] (* _Vincenzo Librandi_, Nov 03 2014 *)

%t LinearRecurrence[{-1, -1},{1, 0},90] (* _Ray Chandler_, Sep 15 2015 *)

%o (PARI) {a(n) = [1, 0, -1][n%3 + 1]} /* _Michael Somos_, Oct 15 2008 */

%o (Haskell)

%o a057078 = (1 -) . (`mod` 3) -- _Reinhard Zumkeller_, Mar 22 2013

%o (Sage)

%o def A057078():

%o x, y = -1, 0

%o while true:

%o yield -x

%o x, y = y, -x -y

%o a = A057078(); [a.next() for i in range(40)] # _Peter Luschny_, Jul 11 2013

%Y Cf. A049310, A010892, A011655.

%Y A049347(n) = a(-n).

%Y Cf. A005043, A011973, A169803, A115139, A091867, A092865, A098925, A102426, A030528.

%K easy,sign

%O 0,1

%A _Wolfdieter Lang_, Aug 04 2000

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified December 9 00:32 EST 2019. Contains 329871 sequences. (Running on oeis4.)